Malaysian social security law in relation to ILO standards: an evaluation of the migrant workers’ rights - Mohamad Amin, Noor Shuhadawati; Ali Mohamed, Ashgar Ali (2015)
This research looks at fundamental principles laid down in the international standards relating to social security. Next, researcher will examine the related ILO standards on social security before exploring the same matter in the light of Malaysian law. The aim of this research is to find out the effect of the ILO on the current Malaysian law despite non-ratification of the same. Besides, the objective of this research is to investigate as to whether the current Malaysian law on social security is at par with the international standards or not. The main concern of this study is on migrant workers in Malaysia thus researcher will relate the migrant workers’ rights to social security in Malaysia under the standards provided by ILO.